2010
DOI: 10.1002/bin.310
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of simultaneous versus sequential presentation of novel foods in the treatment of food selectivity

Abstract: The present study extended the literature on feeding disorders by conducting a comparison of sequential and simultaneous food presentation in the treatment of food selectivity. In the simultaneous condition, a highly preferred food was presented in the same bite with a non-preferred food (NPF), and during the sequential condition, a highly preferred food was delivered as a consequence for acceptance and consumption of NPFs. Generalization and maintenance of food consumption was assessed. Although results for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Poor intake, including number of food bites or volume of food eaten and associated avoidant behaviour towards food and/or mealtimes (Arvedson, 2008;Binnendyk & Lucyshyn, 2009;Casey et al, 2009;VanDalen & Penrod, 2010;Woods, 2010) have been consistently observed in home and laboratory studies. This suggests that reduced food intake is a key characteristic of disordered feeding behaviour in childhood, and indeed an ARFID diagnosis will be unequivocal in children requiring supplementary or total tube-feeding in the absence of physical cause.…”
Section: Introductionmentioning
confidence: 97%
“…Poor intake, including number of food bites or volume of food eaten and associated avoidant behaviour towards food and/or mealtimes (Arvedson, 2008;Binnendyk & Lucyshyn, 2009;Casey et al, 2009;VanDalen & Penrod, 2010;Woods, 2010) have been consistently observed in home and laboratory studies. This suggests that reduced food intake is a key characteristic of disordered feeding behaviour in childhood, and indeed an ARFID diagnosis will be unequivocal in children requiring supplementary or total tube-feeding in the absence of physical cause.…”
Section: Introductionmentioning
confidence: 97%
“…Lag 1/Response blocking increased variety of foods consumed ( M = 2.3). During Lag 2/RB, the variety of food consumed increased from a mean of 2 foods to a mean of 3.3 foods a NTanner and Andreone (2015), CanadaCase study, baseline and interventionN: 1Age: 3Gender: MDiagnoses: ASDClinicalGraduated Exposure and DRA.6-months/100 sessionsIncreased food acceptance from four foods to over 50 foods, with 27 of those foods generalizing to additional settings and people a NVanDalen and Penrod (2010), USACase series, multiple baseline combined with multi-element interventionN: 2Ages: 4 and 5Gender: both MDiagnoses: both ASDClinicalSimultaneous presentation of a non-preferred food with a high-preference food and sequential presentation. NRS with a schedule of reinforcement was also usedBetween 55 and 64 sessionsAt baseline neither participant consumed non-preferred foods.…”
Section: Resultsmentioning
confidence: 99%
“…This study demonstrated that DRA and EE was more effective than RC, EE, and DRA for improving the participant's bite and drink consumption, IMB, and total gram intake. It adds to the research literature evaluating different treatment packages for treating food refusal and selectivity in children (Addison et al, ; Fernand et al, ; Piazza et al, ; Seiverling et al, ; Van Dalen & Penrod, ) as it directly compares these two treatment packages. No differences were observed in child responding between treatments until after the empty spoon condition.…”
Section: Resultsmentioning
confidence: 99%
“…A few studies have compared the effectiveness of different multicomponent packages on child mealtime behavior directly (Addison et al, ; Fernand, Penrod, Fu, Whelan, & Medved, ; Piazza et al, ; Seiverling, Harclerode, & Williams, ; Van Dalen & Penrod, ). Piazza et al () compared two behavioral interventions, simultaneous presentation (i.e., preferred foods presented at the same time as the nonpreferred food) and sequential presentation (i.e., presentation of preferred food after acceptance of the nonpreferred food) on acceptance of nonpreferred foods in three children with food selectivity and pervasive developmental disorder.…”
Section: Introductionmentioning
confidence: 99%